Artificial Bee Colony Approach for MIMO ARX-Laguerre Pole Optimization - Sonker, Smita; Devi, Neeraj (Discontinuity, Nonlinearity, and Complexity, 2026)
In this study, we proposed a method for the pole optimization of the linear Muti Input Multi Output (MIMO)-Laguerre model using artificial bee colonies. The independent and orthonormal Laguerre basis is used to expand the system's inputs and outputs. The artificial bee colony (ABC) technique is used to model MIMO-Laguerre systems and the results are studied. Using this approach, the model parameters for the systems are generated and the algorithm's performance is compared with genetic algorithm and training functions. A numerical simulation to the CSTR Benchmark validates the optimization of Laguerre poles.